The Way to Nicaea - John Behr (USA St. Vladimir's Seminary Press, 2001)
"This first volume treats the initial three centuries of the Christian era. Part I examines the establishment of normative Christianity on the basis of the tradition and canon of the Gospel and briefly sketches the portrait of the Scriptural Christ inscribed in the New Testament. Part II analyzes selected figures from the second century, Ignatius of Antioch, Justin Martyr and Irenaeus of Lyons, considering how they understood Christ to be the Word of God. Part III turns to the third century, treating Hippolytus and the debates in Rome, Origen and his legacy in Alexandria and Paul of Samosata and the Council of Antioch, in a continued examination of Christ as the Word and Son of God. These debates form the background for the controversies and Councils of the following centuries, to be examined in subsequent volumes"--Page 4 of cover
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Theology -- History -- Early church, ca. 30-600; Theology, Doctrinal